Analisis Kualitas Air Desa Nulle Kecamatan Amanuban Barat Kabupaten Timor Tengah Selatan - Mawar, Yuliana Pelewa; Kadang, Luther; de Rozari, Philiphi (Universitas Nusa Cendana, 2022)
Water is one of the most important human needs, there for the availability and of water has to be protected from pollution. The purpose of the study was to determine the quality of the Spring based on physical, chemical and biological parameters in the Tailete, Netbesi and Oenise springs in Tublopo village, West Amanuban district, South Central Timor regency. The research sampling method followed the meet developed on Indonesian National Standard (SNI) and determination of water quality status was based on the storet method accords to the Decree of the Minister of the Environment No. 115 of 2003. The results should physical and chemical parameters in the Tailete, Netbesi and Oenise springs indicate that meet the water quality standards based on the Minister of Health regulation No. 32 of 2017. However, did was not meet Water quality standards detergent and microbiological parameters, coliform in the Tailete and Oenise springs. The quality status of the Tailete and Oenise springs in was clasis moderately polluted with a score of -25. Meanwhile, class A Netbesi springs are classified as meeting water quality standards with a score of 0.